Transtorno de estresse pós-traumático: um estudo fenomenológico-existencial da violência urbana - Cardinalli, Ida Elizabeth (2011)
Urban violence is currently a complex and worrying issue so much so that national and international organizations have been calling for studies in its various aspects. This research was developed with a focus on the impact of urban violence on the health and illness of its victims, based on an overriding concern: explaining and clarifying the meaning and significance of the experience of those who suffered urban violence, such as hold-up and/or express kidnapping. The methodology was based on the existential-phenomenological thinking, in particular Martin Heidegger s, who understands human existence as being-there and being-in-the-world, seeking to understand the experience of victims of urban violence in its entirety. The methods used included interviews with three participants and focal psychotherapy with one with 23 sessions of 50 minutes each. The participants were two men and one woman, all married, and aged between 48 to 53 years. The analysis of the results was organized along two axes: thematic and temporal. The results suggest that the victims of hold-up or express kidnapping show significant distress, when the experience of violence remains trapped in the sense of risk, threat and danger. The impact of violence can also affect the understanding of oneself, of others and the world with the sudden approach of the dimensions of unpredictability, precariousness and vulnerability resulting from a situation of violence. The discussion of the results is extended to possible applications in the Public Health Service. Topics for future research that articulate Clinical Psychology and urban violence are also listed. (Supported by CEPE/PUC-SP)